Iveliz explains it all - Arango, Andrea Beatriz (Random House, 2022)
Young Iveliz relates her seventh-grade year and goals in her poetry journal. She is determined to have a much better first year in middle school than her last year in elementary went, but with her abuela Mimi just having moved from Puerto Rico and having a hard time settling in, her struggle with anger issues, and her mother's inability to understand why Iveliz needs her anxiety medicine, seventh grade is proving very tough indeed.